“We are a ghost in the class.” First Year International Students’ Experiences in the Global Contact Zone - Freeman, Keri; Li, Minglin (Journal of International Students, 2019)
This article draws on data collected during case studies involving six undergraduate international students. It uses the academic literacies framework to examine how international students (re)negotiate their student identities. Based on the concept that Australian university classrooms are global educational contact zones, the study reinforces the urgent need to shift from existing narratives which focus on international students’ perceived language and literacy deficits. Participants demonstrated positive student identities by successfully mediating disciplinary requirements. However, their transition was hindered due to insufficient opportunities for meaningful classroom interactions and lack of academic instruction and feedback. The findings suggest teachers are in the best position to address this gap through classroom pedagogies which accommodate learners from diverse backgrounds and facilitate inclusive learning environments.